Children under 5 years are at risk for tuberculosis after occasional contact with highly contagious patients: outbreak from a smear-positive healthcare worker. Issue 5 (2nd November 2017) - Luzzati, Roberto; Migliori, Giovanni Battista; Zignol, Matteo; Cirillo, Daniela Maria; Maschio, Massimo; Tominz, Riccardo; Ventura, Giovanna; Patussi, Valentino; D'Ambrosio, Lia; Centis, Rosella; Michieletto, Franco; Trovato, Alberto; et al.
The World Health Organization (WHO), jointly with experts from tuberculosis (TB) low-incidence countries, developed a framework for TB elimination [1, 2]. Children under 5 years of age are at risk for tuberculosis after occasional contact with highly contagious patients http://ow.ly/RqAn30fKdGk